ChemInform Abstract: Computational Studies of Atmospherically‐Relevant Chemical Reactions in Water Clusters and on Liquid Water and Ice Surfaces. Issue 17 (April 2015) - Gerber, R. Benny; Varner, Mychel E.; Hammerich, Audrey D.; Riikonen, Sampsa; Murdachaew, Garold; Shemesh, Dorit; Finlayson‐Pitts, Barbara J.
Abstract Review: 53 refs.